Cervical Sagittal Imbalance is a Predictor of Kyphotic Deformity After Laminoplasty in Cervical Spondylotic Myelopathy Patients Without Preoperative Kyphotic Alignment. Issue 4 (February 2016) - Sakai, Kenichiro; Yoshii, Toshitaka; Hirai, Takashi; Arai, Yoshiyasu; Torigoe, Ichiro; Tomori, Masaki; Sato, Hirokazu; Okawa, Atsushi
Abstract : Study Design: A retrospective cohort study. Objective: The aim of this study is to investigate the preoperative factors for postlaminoplasty kyphotic deformity in cervical spondylotic myelopathy (CSM) patients without preoperative kyphotic alignment focused on the cervical sagittal balance. Summary of Background Data: After laminoplasty (LAMP), appropriate decompression may be obtained when cervical lordosis is maintained to allow the posterior shift of the spinal cord. Therefore, LAMP is not suitable for patients with preoperative cervical kyphosis. However, we sometimes encounter patients who developed postoperative kyphosis despite normal preoperative alignment. The risk factors of postlaminoplasty kyphotic deformity for the patients without preoperative kyphotic alignment are not well known. Methods: A total of 174 consecutive patients who received a double-door LAMP for CSM without preoperative kyphotic alignment and completed a 1-year follow-up were enrolled. Cervical lateral X-ray images obtained in the standing position were measured at the preoperative stage and during a 1-year follow-up visit. The radiographic measurements included the following: (1) C2-7 lordotic angle (C2-7 angle), (2) C2-7 range of motion (C2-7 ROM), (3) CGH (center of gravity of the head)-C7 SVA, and (4) C7 slope. The clinical results were evaluated using the Japanese Orthopedic Association score system for cervical myelopathy (C-JOA score). Results: Postoperative kyphotic deformity was observed in 9 patients (5.2%). The recovery rates of the C-JOA scores at the 1-year follow-up period in the kyphotic deformity (+) group were inferior to those of the kyphotic deformity (−) group. The CGH-C7 SVA and advanced age were detected as preoperative risk factors using multivariate analysis. Cutoff values for predicting postlaminoplasty kyphotic deformity were a CGH-C7 SVA = 42 mm and an age of 75 years. Conclusion: Cervical sagittal imbalance and advanced age were the preoperative risk factors for kyphotic deformity after LAMP for CSM in patients without preoperative cervical kyphotic alignment. Level of Evidence: 4